2022
DOI: 10.1021/acscatal.2c00854
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(III)-Catalyzed Oxidative C–H Alkylation of Aniline Derivatives with Allylic Alcohols To Produce β-Aryl Ketones

Abstract: The Rh­(III)-catalyzed C–H oxidative alkylation of aniline derivatives with readily available secondary allyl alcohols using a pyrimidine-directing group, leading to the production of β-aryl ketones, is described. A wide variety of functional groups are tolerated in the reaction. In the reaction with an allyl alcohol bearing a methyl group at the α-hydroxy carbon, such as but-3-en-2-ol (2a), a metal oxidant is not required. In sharp contrast, no reaction occurs when the methyl group in 2a is replaced with ethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 99 publications
0
29
0
Order By: Relevance
“…C–H functionalization of (hetero)­arenes has received sustained attention for the construction of synthetic building blocks and the late-stage functionalization of complex molecules. , However, the transition-metal-catalyzed directed C–H functionalization of (hetero)­arenes with allylic alcohols usually prefers the β-H elimination delivering carbonyl compounds via enol intermediates (Scheme a, left) . The β-OH elimination leading to the desired allyl­(hetero)­arene products is unfavorable due to the low leaving group tendency of the OH group (Scheme a, right).…”
Section: Introductionmentioning
confidence: 99%
“…C–H functionalization of (hetero)­arenes has received sustained attention for the construction of synthetic building blocks and the late-stage functionalization of complex molecules. , However, the transition-metal-catalyzed directed C–H functionalization of (hetero)­arenes with allylic alcohols usually prefers the β-H elimination delivering carbonyl compounds via enol intermediates (Scheme a, left) . The β-OH elimination leading to the desired allyl­(hetero)­arene products is unfavorable due to the low leaving group tendency of the OH group (Scheme a, right).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to make this process more economical and greener, the use of O 2 alone or the combination of catalytic amount of inorganic oxidant with O 2 as the terminal oxidant has been realized by the groups of Huang, [15a] Xi, [15b] Yu, [15c] Wen, [15d] Su, [15e] Jeganmohan [15f–i] and us, [15j] respectively. Meanwhile, with contributions from the groups of Jiang, [16a,c] Glorius, [16b] Kim [16d,e] and others, [16f–l] Cp*Rh(III)‐catalyzed direct alkylation of arene C−H bonds with easily accessible allylic alcohols has received increasing attentionbecause it allows straightforward and efficient construction of synthetically useful ß‐aryl ketones [16m] . Drawing inspiration from these studies, we envisioned that regioselective C−H alkenylation and alkylation at the C8‐position of 1,2,3,4‐tetrahydroquinolines with alkenes and allylic alcohols might be accomplished under similar Rh(III) catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…14 Next, decarboxylation of 3aa in the presence of Ag 2 CO 3 in DMSO afforded benzo[a]phenazine (9) in a 72% yield. 15 The reaction of 3aa with (COCl) 2 in a catalytic amount of DMF followed by reaction with dimethylamine produced N,Ndimethylbenzo[a]phenazine-6-carboxamide (10) with a 64% yield. 16 Furthermore, reduction of 3ba with NaBH 4 produced the corresponding alcohol (11) in a 90% yield.…”
mentioning
confidence: 99%
“…9 Later, Chetani and co-workers described a pyrimidine-directed Rh( iii )-catalyzed C–H alkylation of an aniline derivative with allyl alcohols as a coupling partner (Scheme 1b). 10 Liu et al reported a Rh( iii )-catalyzed oxidative [4+1] annulation of isoquinolines with allyl alcohols leading to the formation of isoindolo[2,1- b ]isoquinolin-5(7 H )-ones (Scheme 1c). 11 To the best of our knowledge, use of allyl alcohols as two-carbon synthons for C–H/N–H annulation reactions has seldom been demonstrated.…”
mentioning
confidence: 99%